Time domain calculation of noise generated by a propeller in a flow - Carley, Michael (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 1997)
In this thesis, the problem of calcultaing the noise from an acoustically subsonic aircraft propeller is approached using a "moving medium" method. An established theory of noise generation by rigid bodies in motion is combined with the moving medium Green's function to develop a linear acoustic formulation for the sound radiated by a body in arbitrary motion in a uniform steady flow of arbitrary orientation.
Keywords: Engineering and Technology, Ph.D.; Ph.D. Trinity College Dublin